Lunar Power Sources: An Opportunity to Experiment - Michele Marrone; Luca Pasqualin; Carlo Giovanni Ferro (Aerospace)
This paper presents a systematic analysis of power generation technologies for a lunar outpost supporting six astronauts. Based on a detailed power budget analysis requiring 65 kWe for life support, scientific equipment, and in situ resource utilization (ISRU), a comparative analysis of solar and nuclear power solutions is conducted. Nuclear fission is identified as the most promising technology based on key criteria, including mass efficiency, reliability, and power density. A parametric study is then conducted to optimize the nuclear reactor design, with particular focus on radiation shielding using lunar regolith and its impact on safety distances. The analysis demonstrates that proper shielding can reduce the required safety distance from over 2.5 km to approximately 90 m while maintaining radiation exposure within acceptable limits. Finally, leveraging insights from existing reactor designs, an optimized configuration is proposed that combines multiple small reactors to meet the unique challenges of lunar power generation while ensuring crew safety and operational redundancy.